The effect of heated tobacco products on metabolic syndrome: A cohort study - Yongho Jee; Sang Yop Shin; Mikyung Ryu; Jonathan M. Samet (Tobacco Induced Diseases)
Introduction Evidence concerning the health effects of using heated tobacco products is needed. The aim of the present study is to investigate the effects of conventional cigarettes (CCs), electronic vaping cigarettes (EVCs), and heated tobacco products (HTPs) on the development of metabolic syndrome.